NF1-mutated melanomas reveal distinct clinical characteristics depending on tumour origin and respond favourably to immune checkpoint inhibitors. (December 2021) - Thielmann, Carl M.; Chorti, Eleftheria; Matull, Johanna; Murali, Rajmohan; Zaremba, Anne; Lodde, Georg; Jansen, Philipp; Richter, Luisa; Kretz, Julia; Möller, Inga; Sucker, Antje; Herbst, Rudolf; et al.
Abstract: Background: NF1 -mutated tumours represent a small subset (10–15%) of melanomas, not sufficiently analysed in large clinical cohorts. This study investigated the largest multicentre collection of NF1 -mutated melanomas to date. Methods: This study analysed a multicentre tumour tissue sample cohort from 266 patients with NF1 -mutated melanoma. Targeted next-generation sequencing of the TERT promoter and 29 relevant melanoma genes was performed. Survival was compared with NF1 wild-type cohorts from the Tissue Registry in Melanoma project (n = 432). Results: Most NF1 -mutated melanoma arose in the head-and-neck region of patients >60 years. NF1 alterations were frequently inactivating, primarily non-sense, less frequently truncating mutations. Non-inactivating NF1 mutations more frequently co-occurred with activating BRAF and RAS mutations. NF1 -mutated tumours had higher numbers of gene mutations and UV signature C>T and CC>TT transitions than BRAF, RAS and triple wild-type melanomas. NF1- mutated acral and mucosal melanomas harboured a different mutation signature and were frequent in women (69% and 83%, respectively), differing from non-acral cutaneous NF1 -mutated melanomas (men 73%, women 27%). Overall survival in stage IV disease was comparable for patients with NF1 -mutated or wild-type melanoma. However, in patients receiving first-line immune checkpoint inhibitor treatment, better median overall survival (mOS) was observed for NF1- mutated than wild-type tumours (mOS = not reached vs mOS = 25.82, p = 0.0154, n = 80 and 432, respectively). Conclusions: Cutaneous, acral and mucosal NF1 -mutated melanomas vary in clinical and genetic characteristics and demonstrate a favourable outcome on immune checkpoint inhibition therapy. Highlights: NF1- mutated melanoma respond favourably to programmed death-1-based immunotherapy. NF1 -mutated metastatic melanoma had a similar overall survival to NF1 wild-type. Non-acral, acral and mucosal NF1 -mutated melanoma are clinically distinct. NF1 -mutated melanomas exhibit a large amount of UV signature mutations.